Health - Seeking Behaviour of Men Living with Prostate Cancer – A Qualitative Study in the Volta Region - Dumor, E.K. (University Of Ghana, 2020)
Prostate cancer (PCa) is the most common male diagnosed cancer and the second leading cause of cancer death globally. The treatment involves huge financial commitments from patients and their families. In Ghana, there is a dearth of literature on the health-seeking behaviour of men living with PCa hence, the need for this study to explore the health-seeking behaviour of men living with PCa in the Volta Region using the Theory of Reasoned Action as a guiding framework. An exploratory descriptive qualitative study design with a purposive sampling technique was employed to recruit ten (10) participants for the study. An in-depth interview was conducted using a semi-structured interview guide. The interviews were audiotaped, transcribed, coded, and analyzed using thematic content analysis techniques. Five major themes emerged: attitude, subjective norms, health-related factors, behavioural intention, and behaviour. The finding revealed that personal beliefs, emotions, and behaviour greatly influenced the participants' attitudes towards health-seeking. The participants sought interventions such as traditional, medical, and complementary therapies. Secrecy due to perceived negative judgment, ignorance, misinterpretation of the early clinical manifestation, and financial difficulties contributed to delayed health-seeking behaviour. Therefore, there is a need for more education on urological conditions especially PCa to promote early health-seeking behaviour
MPhil. Nursing
Keywords: Prostate Cancer; Volta Region